Advantages of use of cascade schemes and metering gear pumps when extruding polymers - Луценко, Ірина Вікторівна; Богатир, Анна Сергіївна; Швед, Микола Петрович; Швед, Дмитро Миколайович (Technology audit and production reserves, 2013)
The article analyzes the major famous schemes of extrusion units. It provides the parameters that characterize and define the extrusion. We have formulated main problems when choosing the design parameters of an extruder. The article presents the constructive decisions for the improvement of mixing capability and increase of productivity at screw extrusion. There are conclusions as to the effectiveness and resource saving when using cascade schemes at modern works. The basic structural execution of cascade units was analyzed. The article provides the comparative characteristics of different types of extruders. We consider the accuracy of metering, the change of pressure and temperature during extrusion of polymers on different types of extruders: screw, screw with a metering gear pump, cascade screw disk, cascade gear disk. We have determined the effectiveness of the use of gear pump by increasing the accuracy of metering and reducing the average temperature of melting.